Multi-omics analysis unravels the dynamics of flavor profile in ‘Queen Nina’ berries and the regulatory mechanism underlying volatile esters - Jingyang Wang; Changyun Zhang; Min Li; Xiucai Fan; Ying Zhang; Jianfu Jiang; Chonghuai Liu; Lei Sun (Food Chemistry: Molecular Sciences)
‘Queen Nina’ is a popular grape variety, but the fruit flavor profile and its evolution and regulatory mechanism remain unclear. The flavor profile of ‘Queen Nina’ was systematically investigated by analyzing the soluble sugars, organic acids, free amino acids, and aroma volatiles at 6 different stages. A total of 55 aroma volatiles were identified, with esters being the predominant volatiles in mature berries. The flavor profile of ‘Queen Nina’ was elucidated by constructing a flavor radar chart based on the results of OAV, which identified 5 volatiles as reliable indicators of berries ripening. Additionally, we identified 29 genes associated with esters metabolism and reported for the first time the involvement of the CXE gene family in aroma esters decomposition in grapes. The results contribute to a more comprehensive understanding of the dynamics underlying the flavor profile of ‘Queen Nina’, thereby providing novel insights into enhancing the grape aroma.